Psychological, cultural and socio-structural factors associated with digital immersion in Chilean adolescents. Issue 1 (2nd January 2022) - León, Miriam; Rehbein, Lucio; Labbé, Christian; Van Deursen, Alexander J. A. M.; Cerda, Cristian
ABSTRACT: Nowadays, adolescents grow up in environments where many aspects of their lives are mediated by digital technologies. The aim of this study was to examine the influence of psychological, cultural and socio-structural factors in the level of digital immersion in adolescents from southern Chile. A non-probabilistic sample of 469 adolescents was collected from schools with different socioeconomic backgrounds. A multigroup analysis was performed using structural equations modelling. The results indicate that family income moderate digital immersion model. Furthermore, for low-income and middle-to-high-income students, the attitude towards the use of digital technologies was the most important factor to predict digital immersion, followed by motivation. However, the results indicate differences between groups by family income in the following model's path: from navigation skills to social skills; motivation to satisfaction; self-transcendence value to social skills; and attitude towards the use of technology to motivation. This study provided an opportunity to move forward in the understanding of the relationship between Chilean adolescents and their technology use. These results indicate the existence of deep cultural changes in Chilean adolescents' life, which are strongly marked by the profuse use of digital technologies. IMPACT SUMMARY a. Prior State of Knowledge: The use of digital technologies has been studied in different contexts, considering diverse population, but adolescents' immersion in digital technologies has not been addressed in the Chilean context. This lack of knowledge might affect a deeper understanding of technology use. b. Novel Contributions: The current study addresses and proposes a new definition of adolescents' digital immersion taking into consideration psychological, cultural and socio-structural factors, allowing a more integrated, and empirically based, approach to the phenomenon. c. Practical Implications: As the use of digital technologies occurs in a complex ecosystem, the findings reached in this study represent relevant data for policy makers, in order to define and promote digital immersion in Chilean adolescents, and other similar contexts.